Shocked confined-granular flow over obstacles. (10th April 2023) - Jaiswal, Yash; Khan, Aqib; Kumar, Rakesh; Kumar, Sanjay
Abstract: Abstract : Interaction of supercritical granular flow with obstacles in a confined channel generates shock waves characterised by a nearly parabolic front of agitated grains in the outer region and a heap of static grains in the inner region. The inner static heap results from granular collapse due to high volume fraction and enhanced collision rate near the obstacle. The present work reports interesting flow structures when granular shock waves are formed on an array of three identical triangular obstacles placed in a rectangular channel at different spacings. It is observed that spacing has a profound influence, resulting in three types of flow structures. Through dimensional analysis, it is found that the normalised shock stand-off distance primarily depends on the Froude number, Fr, and the normalised spacing between the wedges. The experimental data show a strong dependence on these parameters. The normalised shock stand-off distance decreases linearly for small Fr and asymptotically approaches a small value at high Fr . The presence of a new stagnant dome-like structure results in a non-intuitive behaviour of shock stand-off with the wedge spacing. These features are discussed in detail using high-resolution shadowgraphy and the velocity field from particle image velocimetry.